Advancing diabetes treatment: from human beta cell technology to bioartificial pancreas development - Sá, Joana; Sá, Simone; Leménager, Hélène; Costa, Raquel; Onteniente, Brigitte; Soares, Raquel; Ribeiro, Viviana P.; Oliveira, Ana L. (Frontiers in Biomaterials Science, 2025)
In 2021, approximately 537 million people worldwide, primarily in low- and middle-income countries, were affected by diabetes, leading to approximately 6.7 million deaths annually or severe secondary complications including life-threatening hyperglycemia. For nearly 50 years, current therapeutic approaches include full pancreas transplantation and isolated pancreatic islets, more recently, cell therapy such as in vitro generated islets and stem cell derived. The transplantation of pancreatic islet cells can be less invasive than full organ transplantation, however, does not achieve the same rate of functional success due to the low survival of the engrafted cells. Tissue-engineered bioartificial pancreas has been designed to address such issues, improving cell engraftment, survival, and immune rejection problems, with the added advantage that the tissue produced in vitro has an unlimited source of material.